Transposed-letter Neighbor Effects on Different Syllabic Positions on a Lexical Decision Task (Revista de Estudos da Linguagem, 2025)
This study examined the effect of transposed-letter neighborhood (TLN) in different syllabic positions during visual word recognition in Brazilian Portuguese. For this, we conducted two experiments. In the first experiment, 40 college students took part in a lexical decision task with masked priming. The stimuli — disyllabic words and pseudowords — were primed by a nonword created by transposing two letters of the target stimulus. The letter transpositions occurred in different syllabic positions: within the first syllable, within the second syllable, or between the first and second syllables. A control condition with no prime was also included. The dependent variable was reaction time in determining whether the stimulus was a word or not. In the second experiment 31 college students took part in the study, and the control condition involved an identity prime. The results from both experiments revealed that the experimental conditions differed significantly from the control but did not differed statistically among themselves. These results suggest that TLN effects do not vary according to syllabic position. This absence of interaction was interpreted in the light of dual-route models of reading, suggesting that the orthographic route plays a primary role in the TLN effect.